The value of logged tropical forests: A study of ecosystem services in Sabah, Borneo - Nastasia Boul Lefeuvre; Nadine Keller; Pauline Plagnat-Cantoreggi; Elia Godoong; Anne Dray; Christopher David Philipson (Elsevier Ltd, 2022)
Combatting the global threats to climate and biodiversity require further efforts in conserving earth’s key ecosystems such as tropical forests. Today, worldwide conservation strategies have largely focused on protecting old-growth forests. Yet logged forests are more widespread than old-growth forests and harbour huge amounts of biodiversity and carbon stores, providing many ecosystem services and functions. In Borneo, logged forests support the livelihood of half a million indigenous people. Empowering these communities to manage logged forests can result in ecological, social and economic benefits. This study took place in Sabah, Malaysian Borneo, and focused on logged forests. We investigated how community members value ecosystem services (ES) in terms of importance for their lives, and explored factors influencing their valuation. We combined a qualitative analysis of semi-structured interviews with a statistical analysis of respondents’ preferences for ES. We present three key findings: 1. Clean water, clean air, regulation of temperature, flood and erosion are the ES ranked as the most important by all community members regardless of their spatial and socio-demographic backgrounds, 2. Prioritization for other ES varied according to members’ age, gender, ethnicity, dependence on forest resources and distance to forest, 3. Community members’ priorities for ES align with the ecological literature that these services are retained by logged forest. Our results emphasize the need to promote people-centred approaches to design sustainable conservation policies of logged forests in Sabah.